Firearms Law and Fatal Police Shootings: A Panel Data Analysis - Nguyen, Diep Bich (2021)
Among industrialized countries, U.S. holds two somehow inglorious records: the highest rate of fatal police shootings and the highest rate of deaths related to firearms. The latter has been associated with strong diffusion of firearms ownership largely due to loose legislation in several member states. The present paper investigates the relation between firearms legislation\diffusion and the number of fatal police shooting episodes using a seven-year panel dataset. While our results confirm the negative impact of stricter firearms regulations found in previous cross-sectional studies, we find that the diffusion of guns ownership has no statistically significant effect. Furthermore, regulations pertaining to the sphere of gun owner accountability seem to be the most effective in reducing fatal police shootings